Food Safety Policies Implementation in a Fish Port Complex in the Philippines: Stakeholders’ Perceptions - Jesus Briones; Kim Joy L Bueno; Angelita B Jose; Maria Victoria M Fernando; Romeo M Lapaz Jr; Sheryl D Hermoso; Hay Ann Rosario; Raymond T Buzon (Logistic and Operation Management Research (LOMR), 2026)
Ensuring food safety in fish port complexes is vital for public health and the sustainability of the Philippine seafood industry. Anchored in Stakeholder Theory, this study investigated food safety policy implementation in a premier Philippine fish port by evaluating how the alignment of diverse interests determines success. Using a descriptive-comparative and correlational design, the researchers surveyed 383 respondents, including employees, brokers, and buyers. Data were analyzed using frequency and percentage, weighted mean, median, interquartile range, Kruskal-Wallis H, and Spearman’s rank-order correlation. Results revealed a demographic dominated by experienced brokers and daily fish buyers. While storage and handling were perceived as highly implemented, sanitation received the lowest ratings. A significant perceptual gap exists, with internal stakeholders rating hygiene more favorably than external buyers. Although a moderate positive correlation confirmed that active enforcement drives compliance, stakeholders identified high supply costs, infrastructure deficits (specifically clean water access), and peak workloads as primary barriers. To bridge the gap between policy and practice, the study proposes a strategic roadmap focusing on infrastructure retrofitting, digital traceability, and participatory governance through a Food Safety Council. Theoretically, this research advances Stakeholder Theory by demonstrating that alignment is a measurable indicator of policy efficacy. Practically, it provides port authorities with a localized framework to move beyond performative compliance toward a sustainable, high-integrity seafood supply chain.